(In)Subordinate Planning: A Decolonial Tool for Marginalized Urban Areas - Claudia Seldin (Nuevo mundo - Mundos Nuevos, 2024)
The city of Rio de Janeiro (Brazil) has various socially and historically marginalized areas, such as peripheral neighborhoods and favelas, which lack traditional leisure and cultural spaces. These areas are often seen as subaltern, neglected by the state, and not sufficiently contemplated in public policies. Consequently, local inhabitants frequently have to come up with improvised solutions, using their own resources to design and build sociocultural spaces. While much has been written about the practice of self-building in favelas, not enough research has been done from the urban planning/urban studies perspective pairing this practice with the decolonial theory hailing from South America. This article aims to frame the collective self-building of sociocultural spaces in favelas as a type of “insubordinate planning.” The concept of “insubordinate planning” is suggested here as part of a broader decolonial toolbox, regularly used by marginalized urban communities to persist and ensure their right to the city. To illustrate the connection between self-building, sociocultural spaces, insubordinate planning, and decolonial theory, the case study of the Sitiê Park in the Vidigal Favela is presented. This study was conducted through ethnography for a year and proves that decolonial principles are intrinsic to favela dwellers when it comes to building persistent spaces.